INTERNATIONAL CLASSIFICATION OF FUNCTIONALITY, DISABILITY AND HEALTH IN PROCESS OF OUTPATIENT INTERVENTION IN PATIENTS WITH PULMONARY TUBERCULOSIS (REMUNOM, 2024)
Pulmonary tuberculosis (TB) symptoms impact an individual's health, being associated with specific functional disabilities, adverse reactions and symptoms. Objective: To analyze the functional impact of the disease, seeking to identify the functions, body structures, self-care, environmental and personal factors, thus providing support for adherence treatment and improving the quality of life. Method: Descriptive, cross-sectional, quantitative study. conducted with users registered in the Family Health Program of the city of Rio de Janeiro, diagnosed with TB. The ICF and COPM questionnaire was applied and an interview was conducted to complement the data. Results: 49 patients with TB, with age between 18 to 60 years participated. The ICF and the COPM questionnaire have been shown to be an important instrument for assessing functional capacity and abilities to perform activities of daily living (ADL) and instrumental (IADL). It is possible to identify the biopsychosocial impact and functional limitation of the disease. The most relevant functional disabilities are present in the domains function and body structure, activities, participation and environmental factors. Conclusion: It was concluded that the ICF and COPM proved to be a viable instrument for the assessment of disability in ADL and IADL of the patient with TB.